Application of Appropriate Technology for Making Organic NPK Fertilizer by Utilizing Palm Oil Mill Waste in Bekiung Village (Talenta Publisher Universitas Sumatera Utara, 2024)
Bekiung is one of the villages in Langkat Regency. Farmers in this village generally cultivate a lot of oil palm plants. The waste is quite large and causes environmental pollution problems. On the other hand, experience problems in the form of scarcity and expensive synthetic fertilizers, subsidized fertilizers that are no longer available, and less fertile soil. This is due to the lack of knowledge and skills of farmers, limited advice and infrastructure in waste processing. The aim of this activity is to increase farmers' knowledge and skills in processing palm oil waste into organic NPK fertilizer, open farmers' insight into the importance of organic fertilizer as a diversification of synthetic fertilizer which is beneficial for soil properties and increase the independence of partners in waste processing. The solution offered to overcome this problem is the introduction of appropriate technology and processing palm oil factory waste into organic NPK fertilizer. The methods used in this activity are socialization and direct practice in the field. The results obtained were the introduction and delivery of technology transfer equipment in the form of a hummer mill, conveyor and simple filter, training and assistance in making organic NPK fertilizer up to packaging. The conclusion of this activity is that it is a beneficial activity for partners because it increases the understanding and independence of partners in processing palm oil mill waste into organic NPK fertilizer which can overcome the problem of the availability of scarce and expensive fertilizer.